2015
DOI: 10.1016/j.ajic.2014.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Selecting models for a respiratory protection program: What can we learn from the scientific literature?

Abstract: Background An unbiased source of comparable respirator performance data would be helpful in setting up a hospital respiratory protection program. Methods The scientific literature was examined to assess the extent to which performance data (respirator fit, comfort and usability) from N95 filtering facepiece respirator (FFR) models are available to assist with FFR model selection and procurement decisions. Results Ten studies were identified that met the search criteria for fit, whereas 5 studies met the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
0
26
0
2
Order By: Relevance
“…The fit test passing rate differed a great deal between the different respirator models, with four models having a pass rate of 80% or more and two having a pass rate of 30% or less although all of the them were certified according to the European Standard EN 143:2000 [20]. A varying pass rate between respirator models has also been shown in several other studies [15], [16], [17], [19], [21], [22], [23], [24], [25]. When it comes to respirators, it is clear that one model or one size does not fit all.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The fit test passing rate differed a great deal between the different respirator models, with four models having a pass rate of 80% or more and two having a pass rate of 30% or less although all of the them were certified according to the European Standard EN 143:2000 [20]. A varying pass rate between respirator models has also been shown in several other studies [15], [16], [17], [19], [21], [22], [23], [24], [25]. When it comes to respirators, it is clear that one model or one size does not fit all.…”
Section: Discussionmentioning
confidence: 71%
“…In addition, with fewer models to choose from, it is more easy for the workers to remember which respirator they passed the test with, minimizing worker confusion about which respirator to wear. Shaffer and Janssen [25] conducted a literature study and concluded that although there does not appear to be a single best-fitting filtering facepiece respirator, studies demonstrate that fit testing programs can be designed to successfully fit nearly all workers with existing products. Five of the smelter workers did not pass the fit test with any of the five or six respirators with which they performed the test, although four of them had a total FF ≥ 100.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, discomfort was the most common reason given by HCWs for improper use of respirators [27]. Perceptions of increased body heat when wearing the N95 FFR are likely not…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the quantitative fit test is done by using ambient aerosols to numerically estimate how well the N95 fits the user by measuring the aerosol particle ratio outside (C o ) and inside (C i ) the device. Nonetheless, studies demonstrate that fit testing with either method provides the expected levels of protection (Shaffer & Janssen 2015). Studies have shown that varying pass rates for fit tests range from 10% to 80% indicating that one size does not fit all (McMahon et al 2008, Winter et al 2010, Huh et al 2018.…”
Section: Which Model Should I Choose?mentioning
confidence: 99%